Study to the Decomposition and Forensic Insect Succession Pattern on Rabbit Carcasses Placed Indoor and Outdoor in Al Kufa City -Iraq - Suhad Hameed H. Albushabaa (Journal of Global Pharma Technology, 2018)
This study was conducted at the Department of Biology, Faculty of Science, Al-Kufa University, Al-Kufa City / Najaf- Iraq. The fauna of insects associated with rabbit carcasses(Lepus cuniculus) placed indoor and outdoor habitats, and their succession patterns were investigated. A total of 1589 adults and immature insects were collected during summer and autumn, 2016, representing in 3 orders and 7 families. Diptera, Coleoptera and Hymenoptera comprise79.11%, 12.21% and8.68% .A total of 630 insect specimens was collected from rabbit carcasses placed indoor. Diptera, Coleoptera and Hymenoptera comprised 80.2%, 11.7% and 8.1%, respectively. While, 959 insect specimens were collected from rabbit carcasses placed outdoor .Diptera, Coleoptera and Hymenoptera comprised 78.4%, 12.5% and 9.1%, respectively. Four stages of decomposition were observed fresh, bloated, decay and dry. The duration of it varies with temperature and relative humidity of each season. The total period of decomposition was 15 and 19 days during Summer in carcasses placed outdoor and indoor respectively (Mean temperature 40 ○C and RH between 10% and 20%) ,while reaching 18 and 25 days during Autumn in carcasses placed outdoor and indoor respectively, (mean temperature 29○C and RH between 54% to 64% ).The results showed that the succession pattern of insect associated with the stages of decomposition was similar between indoor and outdoor habitats with differences in the timing of insect colonization were observed between the two habitats within trials for Summer and Autumn .Also, Chrysomya albiceps was the first insect attracting to the carcass during the fresh stage in both habitats and it was the most abundant fly colonized the carcasses in both habitats but most number at outdoor, followed by Musca domestica. In general, it was appeared that the numbers of forensic insect species which colonize rabbit carcasses were increased outdoor and decreased indoor. Moreover, they were higher numbers during the autumn season than the summer season.Keywords: Outdoor; Indoor; Succession; Rabbit; Carcass; Al-Kufa.